Examining the Effects of Environmental Management Accounting and Social Disclosure on Firm Value - Meilan, Ria; Susanti, Alifi Tria; Sochib, Sochib (Politeknik Raflesia Press, 2024)
Abstract— Examining the connection between social responsibility disclosure and environmental management accounting in raising business value is the primary goal of this study. This study makes use of secondary data gathered from financial statements and sustainable reports in addition to the panel data method, which employs a common impact approach. Using a purposive sampling technique, 190 mining and manufacturing companies that regularly release annual financial statements and sustainable reports during the observation period are selected for the sample of mining and manufacturing companies for the 2019–2023 observation period. With Eviews analysis tools, quantitative data analysis methods are applied. The results of this investigation demonstrate that while social responsibility disclosure affects business value, environmental management accounting has no effect on it. The firm value is impacted by both independent variables at the same time, though. This demonstrates how dedicated the business is to sustainability through social and environmental values. Companies are voluntarily obligated to be socially and environmentally responsible, according to stakeholder theory and the notion of legitimacy, which are the theoretical implications of the study's findings. As stakeholders use information disclosure to evaluate the company's performance, it has also become an essential component of the business. Regulations pertaining to social responsibility and environmental management disclosure requirements can be improved by the government.